2014
DOI: 10.17705/1jais.00378
|View full text |Cite
|
Sign up to set email alerts
|

IT-Enabled Knowledge Creation for Open Innovation

Abstract: Open innovation is increasingly important for researchers and practitioners alike. Open innovation is closely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 66 publications
(94 reference statements)
0
29
0
Order By: Relevance
“…Eseryel and Eseryel (2013) found that in virtual information systems development teams, the action-based leaders influence the team's vision and strategy for technology development by "significantly contributing to the software development effort… over long periods of time" (p.109). While knowledge creation and sharing has been important for virtual teams, such as open source software teams (Eseryel, 2014), Faraj et al (2015) connected this behavior to leadership and showed that individuals perceived as leaders in a software team contribute to knowledge by providing software code, meaning they contribute to the software development by doing work, not only by providing technical knowledge and guidance. This focus on work is different from traditional leadership theory's view of leaders who provide influence by communicating a vision or strategy, rather than by doing work that achieves a vision and strategy piece by piece over time.…”
Section: Leadership In Virtual Teams: Functional Theories Of Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Eseryel and Eseryel (2013) found that in virtual information systems development teams, the action-based leaders influence the team's vision and strategy for technology development by "significantly contributing to the software development effort… over long periods of time" (p.109). While knowledge creation and sharing has been important for virtual teams, such as open source software teams (Eseryel, 2014), Faraj et al (2015) connected this behavior to leadership and showed that individuals perceived as leaders in a software team contribute to knowledge by providing software code, meaning they contribute to the software development by doing work, not only by providing technical knowledge and guidance. This focus on work is different from traditional leadership theory's view of leaders who provide influence by communicating a vision or strategy, rather than by doing work that achieves a vision and strategy piece by piece over time.…”
Section: Leadership In Virtual Teams: Functional Theories Of Leadershipmentioning
confidence: 99%
“…Empirical studies of self-managing teams support this view. Eseryel (2014) found that while all team members provided some knowledge and leadership to the team, the core team members provided visibly more leadership regarding the resolution of critical issues, which were central to the success of the team. Similarly, while Faraj et al (2015) found functional leadership was distributed, they identified a second pattern, namely, that among the identified leaders, the top few received disproportionately large share of the leadership vote, showing that a second type of more centralized leadership.…”
Section: Visionary Leadership Is Most Effective In Changing Structurementioning
confidence: 99%
“…In these directions, product structure design is an essential part of manufacturing enterprises, which includes mechanical design basis, material forming and other contents, which needs to be strengthened; product form design is the traditional direction, which does not need to be adjusted greatly, while its contents can be combined with local cultural, creative and tourism industry to set up its own characteristics; interaction design and visual design mainly involve the content of graphic design, which can be optimized, integrated with the current rapid development of AI product interface design, Internet, mobile Internet and other directions [8]. By combined with the forefront of science and technology, interactive and visual design not only updated its own content, but also provided a good foundation for scientific research and student employment [9].…”
Section: Specific Direction Of Id Subdivisionmentioning
confidence: 99%
“…With open innovation, the inrush and outflow of knowledge is exploited for innovation. In the field of information systems, open innovation is closely related to software development (Eseryel, 2014).…”
Section: A Innovation Resourcementioning
confidence: 99%